Pumilio RNA-Binding Family Member 1 Plays a Promoting Role on Pancreatic Cancer Angiogenesis - Haisu Dai; Yan Jiang; Zhipeng Liu; Xingxing Su; Yishi Yang; Zhiyu Chen (Canadian Journal of Gastroenterology and Hepatology)
Our previous studies showed that Pumilio RNA-binding family member 1 (PUM1) gene is abnormally expressed in pancreatic cancer (PC) tissues, and its knockdown suppresses the growth and metastasis of PC cells. Here, we aimed to further investigate its role in angiogenesis. Immunohistochemical assays were carried out to analyze CD31 and PUM1 expression levels in PC tissues and in subcutaneous xenograft tumors. CD31 levels in PC tissues are expressed as microvessel density (MVD). MVD value was positively correlated with PUM1 protein expression. PUM1 was successfully overexpressed or silenced in the PC cell lines. The proliferation, migration, invasion, and tube formation ability of HUVECs were enhanced when cocultured with PC cells overexpressing PUM1. PUM1 overexpression increased extracellular and intracellular VEGFA protein levels in PC cells. Moreover, angiogenesis-related signaling in HUVECs was activated when HUVECs were cocultured with PC cells overexpressing PUM1. Nevertheless, PC cells silenced with PUM1 had the opposite effect. Moreover, subcutaneous xenograft tumors overexpressing PUM1 have the higher expression level of CD31, while subcutaneous xenograft tumors silencing PUM1 have the lower expression level of CD31. In conclusion, PUM1 in PC cells may play a promoting role in PC angiogenesis. PUM1 may be a new regulator of angiogenesis in PC cells.